Pеndaftaran tanah sistеmatis terhadap akta tеrutang pajak - Yuliana Fatma Ira Crisantika; Imam Koeswahyono; Supriyadi Supriyadi (Jurnal Cakrawala Hukum, 2021)
This article has the intent and purpose to find out the implementation of PRONA systematic land registration for the deed of transfer of land rights that are tax payable, specifically related to Income Tax (PPh) and Land Acquisition Fees (BPHTB) which are the obligations of the parties and are registered through systematic land registration was carried out in Ternyang Village, Sumberpucung District in 2009. However, the obstacles that occurred in the field were different from the turus hamlet, the village community was more cooperative regarding physical data. Nature in Ternyang village is indeed a lot of uneven shape, so it takes more time, to determine the appropriate land boundaries. Bookkeeping of rights or storage of documents constituting evidence shall be marked with identification and kept at the Land Office as an integral part of the general register. In accordance with the provisions of Government Regulation Number 24 of 1997 concerning Land Registration, article 39 paragraph (1) point g, PPAT/PPATS may not sign the deed before the tax obligations are fulfilled and the official who gives the land rights before the tax obligations are fulfilled.How to cite item: Crisantika, Y., Koeswahyono, I., Supriyadi, S. (2021). Pеndaftaran tanah sistеmatis terhadap akta tеrutang pajak. Jurnal Cakrawala Hukum, 12(2), 168-177. doi:https://doi.org/10.26905/idjch.v12i2.5810